Experimental measurement of transmission performance: Sensitivities to hardware design and test implementation - Barnaby, G.; Yon, J. M.; Burgess, S. C.; Hicks, B. J.; Wragge-Morley, R. T. (Journal of Science and Cycling, 2024)
The performance of bicycle transmissions is of interest to the cycling sector for both elite racers and amateur hobbyists. Significant efforts are made by professional teams and individual cyclists to maximise the performance of transmission through equipment choices, gearing selection, and choice of lubrication. Correct selection can improve the physiological efficiency of a rider, increase the power efficiency of a transmission, and better the longevity of components.